HUBUNGAN LAMA KERJA PERAWAT DENGAN KEPATUHAN PERAWAT DALAM PENGISIAN SURGICAL SAFETY CHECKLIST - Siti Chotimah; Leni Wijaya (Jurnal Kesehatan dan Pembangunan, 2022)
Background: Hospital patient safety is a system where the hospital makes patient care safer which includes risk assessment, identification and management of matters relating to patient risk, reporting and analysis of incidents. Death and complications from surgery can be prevented. One way to prevent this can be done with a surgical safety checklist. Surgical safety checklist is a checklist to provide safe and quality surgery to patients. Objective: to find out whether there is a relationship between the length of work of nurses and nurses' compliance in filling out the surgical safety checklist in the operating room of the Musi Medika Cendikia Hospital in Palembang 2021. Methods: The design of this study was a descriptive study with a cross sectional approach. The population in this study were all 17 nurses in the operating room of the Musi medika Cendikia Hospital in Palembang, using the total sampling method. Collecting data using observation sheets. Data analysis used univariate and bivariate analysis with chi square test analysis. Result: there is a relationship between length of work and compliance in filling out the surgical safety checklist at Musi Medika Cendikia Hospital Palembang (p value = 0.022 < 0.05). Suggestion: it is hoped that the hospital can improve the quality of service and improve the skills and expertise of nurses in handling patients, so that they can improve the competence of nurses in filling out the surgical safety checklist.